Principles of distributed systems : 18th International Conference, OPODIS 2014, Cortina d'Ampezzo, Italy, December 16-19, 2014. Proceedings - Querzoni, Leonardo; Shapiro, Marc; Aguilera, Marcos K. (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 18th International Conference on Principles of Distributed Systems, OPODIS 2014, Cortina d'Ampezzo, Italy, in December 2014. The 32 papers presented together with two invited talks were carefully reviewed and selected from 98 submissions. The papers are organized in topical sections on consistency; distributed graph algorithms; fault tolerance; models; radio networks; robots; self-stabilization; shared data structures; shared memory; synchronization and universal construction.